Pilot Study of a Novel Therapeutic Approach for Refractory Advanced Stage Folliculotropic Mycosis Fungoides - Christina A. Guzzo; Neha N. Jariwala; Paul L. Haun; Kelly M. MacArthur; Christen M. Mowad; Elisabeth G. Richard; Joseph P. Holton; Alain H. Rook (Medical Journals Sweden, 2020)
Folliculotropic mycosis fungoides is a variant of cutaneous T-cell lymphoma characterized as having a folliculocentric infiltrate of malignant T cells along with a worse prognosis in comparison to the epidermotropic variants. Patients with advanced forms of folliculotropic mycosis fungoides are often poorly responsive to both skin-directed as well as to systemic therapies. We report here a high response rate using a novel therapeutic regimen combining interferon gamma, isotretinoin in low dose and topical carmustine, and in some cases concomitant skin-directed therapies, among 6 consecutive patients with refractory folliculotropic mycosis fungoides with stages IB through IIIB who had previously failed both topical and systemic therapies. The potential mechanisms of this multimodality approach are discussed.